Pre-Reading Visual Analysis Activity: William Holman Hunt’s The Awakening Conscience (1853) - Hueso-Vasallo, Manuel (My University, 2024)
The following is a method I’ve employed in several subjects in the degree in English Studies at the University of Málaga, more specifically in the subjects “Literatura Inglesa I (Novela)” y “Literatura Inglesa III (Poesía)”. This practice has as its main aim to introduce students to the Victorian era (1837-1901) visually. To achieve this, I show students William Holman Hunt’s painting The Awakening Conscience (1853) and guide them through an analysis of its symbolism and themes. Afterwards, I encourage them to relate what they have learned to the literature and cultural concerns of the period. This method succeeds in helping students to understand some of the main issues they need to pay attention to when we start analysing either the novels or the poetry of the period. The activity, carried out in English, is detailed below.
An Introduction to Literary Analysis in the Victorian Era
Keywords: Literatura inglesa - S.XIX; Visual and literary analysis; Victorian literature; Pre-Raphaelite painting